Analysis of Regional Financial Management of North Bengkulu District Towards Regional Independence in The Autonomy Era - Yohanes Susanto; Shinta Wiji Rahayu (Ilomata International Journal of Management, 2021)
The purpose of this study was to determine the extent to which the financial management of the North Bengkulu district affected regional independence. In this study researchers used secondary data with techniques of collecting data from relevant agencies and using the method of analysis of regional financial independence. The results showed that North Bengkulu Regency was still not at the level of being able to finance its own household, the level of independence of North Bengkulu district during 2012-2019 was at a low level of independence and was still very dependent on the central government. Keywords: Regional Autonomy, Financial Management, Financial Independence